2019
DOI: 10.1016/j.neuron.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Feedback Links Lipid Synthesis to Synaptic Vesicle Pools in Drosophila Photoreceptors

Abstract: Neurons can maintain stable synaptic connections across adult life. However, the signals that regulate expression of synaptic proteins in the mature brain are incompletely understood. Here, we describe a transcriptional feedback loop between the biosynthesis and repertoire of specific phospholipids and the synaptic vesicle pool in adult Drosophila photoreceptors. Mutations that disrupt biosynthesis of a subset of phospholipids cause degeneration of the axon terminal and loss of synaptic vesicles. Although dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 80 publications
3
35
0
Order By: Relevance
“…Tsp39D knockdown resulted in small SGs, yet this phenotype is not fully suppressed by expression of CD63-GFP, indicating that the role of Tsp39D in SG maturation is distinct from Tsp29Fa. On the other hand, Tsp39D expression is crucial for maintenance of synaptic vesicles in Drosophila photoreceptor cells (Tsai et al, 2019), suggesting that CD63 homologues might carry out analogous functions in regulated secretion in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Tsp39D knockdown resulted in small SGs, yet this phenotype is not fully suppressed by expression of CD63-GFP, indicating that the role of Tsp39D in SG maturation is distinct from Tsp29Fa. On the other hand, Tsp39D expression is crucial for maintenance of synaptic vesicles in Drosophila photoreceptor cells (Tsai et al, 2019), suggesting that CD63 homologues might carry out analogous functions in regulated secretion in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the morphology of the lamina cartridge, the organized synaptic modules where R1-R6 photoreceptors project axons to, in pect 29 flies. The structure of the lamina cartridge was intact and mitochondria were normal in pect 29 flies, although synaptic vesicles were disrupted ( Fig 5E ) [ 25 ]. We compared ATP levels between wild-type and pect 29 retinas to assess mitochondrial function and found similar ATP levels in pect 29 mutants and controls.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study also identified recessive lethal mutations in pect and demonstrated that the biosynthesis of specific phospholipids is linked to neurodegeneration and synaptic vesicle loss in adult Drosophila photoreceptors [ 25 ]. In pect omb593 mutants levels of PE 34:1 and PE 36:2 were reduced, but the overall proportions of PE species were not significantly changed, whereas we detected a significant reduction in total cellular PE levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations